Attitude Development of Elementary School Students with the Character Education-based Discovery Learning Model - Hendrizal Hendrizal; Chandra Chandra; Annisa Kharisma (Universitas Pendidikan Ganesha, 2022)
Nowdays technological developments have had a major influence on the lives of Indonesian Muslim children. The change in attitude is going in an unexpected direction. Children tend to be negative in everyday life. The number of children who have the courage to show disrespect is increasing. In fact, violence against peers is increasingly emerging among elementary school age children. Therefore this study aims to analyze the role and influence of the character education-based discovery learning model on the development of attitudes of Indonesian Muslim children who are in elementary school. The research objective can be achieved by conducting experimental research with a two-way ANOVA test. The population of this research is fourth grade elementary school children. The research sample was taken by random sampling. The instruments used in this study were validation sheets, observation sheets, interviews, assessment sheets, student response questionnaires, and evaluation sheets among others. The research findings show that the character education-based discovery learning model has an effect on scientific thinking and the development of responsible and caring attitudes for Indonesian Muslim children. The role of the character education-based discovery learning model on the development of the attitudes of Indonesian Muslim children, namely the character education-based discovery learning model can build an attitude of responsibility and care in the learning process.